AsiaPacifiQueer : rethinking genders and sexualities - Martin, Fran, 1971-; McLelland, Mark J., 1966-2020; Yu, Audrey (Urbana : University of Illinois Press, 2008)
"A multidisciplinary, multicultural reassessment of gender and sexuality in the Asian Pacific"--Publisher's description
Introduction / Fran Martin, Peter A. Jackson, Mark McLelland, and Audrey Yue -- Embodied masculinities of male-male desire : the homo magazines and white-collar manliness in early 1970s Japan / J. Darren Mackintosh -- Lilies of the margin : beautiful boys and queer female identities in Japan / James Welker -- Grrrl-queens : on-kotoba and the negotiation of heterosexist gender language norms and lesbo(homo)phobic stereotypes in Japanese / Claire Maree -- Politics and islam : factors determining identity and the status of male-to-female transsexuals in Malaysia / Yik Koon The -- Recognition through mis-recognition : masculine women in Hong Kong Kam Yip Lo Lucetta -- Being a young tomboy in Hong Kong : the life and identity construction of lesbian schoolgirls / Carmen Ka Man Tong -- The romance of the queer : the sexual and gender norms of Tom and Dee in Thailand / Megan Sinnott -- Bad-assed honeys with a difference : South Auckland Fa'afafine -- Talk about identity / Heather Worth -- Villa, Montano, Perez : postcoloniality and gay liberation in the Philippines / J. Neil C. Garcia -- Bading na bading : evolving identities in Philippine cinema / Ronald Baytan -- Representation, politics, ethics : rethinking homosexuality in contemporary Korean cinema and discourses / Jin-Hyung Park -- Lesbianism and Taiwanese localism in the silent thrush / Teri Silvio -- How to be queer in Taiwan : translation, appropriation, and the construction of a queer identity in Taiwan / Song Hwee Lim -- King Victoria : Asian drag kings, postcolonial female masculinity, and hybrid sexuality in Australia / Audrey Yue.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Homosexuality -- Asia; Gay people -- Asia; Gay people in popular culture -- Asia; Homosexualité -- Asie; Personnes homosexuelles -- Asie; Personnes homosexuelles dans la culture populaire -- Asie; SOCIAL SCIENCE -- Gay Studies; SOCIAL SCIENCE -- Ethnic Studies -- General; Gay people; Homosexuality; Asia; Homosexualität; Asiatisch-Pazifischer Raum; Sexualitet -- identitet -- genus -- Asien; Populärkultur.; Homosexualitet -- lesbianism; Homosexualitet -- Asien; Homosexuella -- Asien; Populärkultur -- homosexuella; Asian LGBTQ+ people; LGBTQ+ culture; Gender identity; Aufsatzsammlung